1974
DOI: 10.1172/jci107769
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the In Vivo Effects of Antibody INTERACTION OF IgM ANTIBODY AND COMPLEMENT IN THE IMMUNE CLEARANCE AND DESTRUCTION OF ERYTHROCYTES IN MAN

Abstract: A B S T R A C T Purified human IgM isoagglutinins wereutilized to sensitize 'Cr-labeled erythrocytes so as to produce a known number of complement-fixing sites.These cells were then reinfused into the erythrocyte donor. A minimum of 20 Cl-fixing sites/erythrocyte were required for decreased survival. As the amount of antibody coating the erythrocytes was increased, a larger percentage was sequestered. With 80 Cl-fixing sites, more than 75% of the injected erythrocytes were removed from the circulation within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(69 citation statements)
references
References 31 publications
4
65
0
Order By: Relevance
“…Approximately 550-800 C3b molecules per red cell are required to activate the hepatic clearance mechanism through Kupffer cells. 20,21 CD55 or DAF is a GPI-anchored protein that is also absent from the surface of the PNH red cell. CD55 is a complement regulatory protein that plays a key role in inhibiting the generation of C3b by regulating the formation of the C3 convertases and accelerating their dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 550-800 C3b molecules per red cell are required to activate the hepatic clearance mechanism through Kupffer cells. 20,21 CD55 or DAF is a GPI-anchored protein that is also absent from the surface of the PNH red cell. CD55 is a complement regulatory protein that plays a key role in inhibiting the generation of C3b by regulating the formation of the C3 convertases and accelerating their dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Schreiber and Frank (44,45) originally demonstrated that erythrocytes coated with cold agglutinin IgG/IgM and complement C3b are cleared/sequestrated rapidly by phagocytes in the spleen and liver. Other investigators have subsequently shown that erythrocytes bound by immune complexes opsonized with complement C3b are quickly stripped off by phagocytic cells, leaving behind C3dg fragments that are covalently bound on cells (43,46,47). Nevertheless, it is possible, and perhaps likely, that some erythrocytes coated with C3-derived ligands may be cleared from the circulation during these processes before completing a 120-day life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of G3-sensitized erythrocytes is followed by a triphasic clearance curve (23,24). There is an initial rapid clearance of cells from the circulation due to attachment to C3 receptors of RES cells, primarily hepatic macrophages (Kupffer cells).…”
Section: Resultsmentioning
confidence: 99%
“…In the normal animal virtually all the cleared cells were returned to the circulation as the membrane-bound C3 was cleaved. When these studies were repeated in man (23,24) it was found that human macrophages behaved as if they were partially activated. A portion of the C3-coated erythrocytes were cleared from the circulation, but many were phagocytosed.…”
Section: Resultsmentioning
confidence: 99%